Occurrence and distribution of mating types of Phytophthora species causing black pod disease of cocoa - R CHANDRAMOHANAN, P. CHOWDAPPA and (Indian Phytopathology, 2002)
The mating types of isolates of P. palmivora, P. capsici and P. citrophthora (which cause black pod disease of cocoa) collected from various localities of Kerala and Karnataka states, India, were determined by pairing them with known A1 and A2 mating types of P. palmivora, P. capsici and P. meadii. Isolates of P. palmivora and P. capsici produced oospores when paired intra- and inter-specifically with either A1 and A2 mating types of P. palmivora, P. capsici and P. meadii, whereas the isolates of P. citrophthora did not produce oospores. Both A1 and A2 mating types were found among the isolates of P. palmivora and P. capsici. A2 mating type was predominant in P. palmivora and A1 in P. capsici. A2 mating types of P. palmivora were predominant in all the districts of Kerala and Karnataka states, India. Both A1 and A2 mating types of P. palmivora and A1 mating types of P. capsici were found in certain localities of Kerala state from where P. citrophthora isolates were collected. The occurrence of both mating types of different species in the same locality reveals the possibility of intra- and inter-specific hybridization in nature and the formation of new strains. This is the first report of the occurrence of mating types of Phytophthora species causing black pod disease of cocoa in India.